The Status of School Water, Sanitation, and Hygiene Services in Addis Ababa, Ethiopia: Progress Towards Achieving the SDG 6 - Abayneh Melaku; Bezatu Mengistie; Taffere Addis (Environmental Health Insights, 2023)
Background: The provision of safe water, sanitation, and hygiene (WASH) facilities and services for schools is vital to students’ health, development, and educational performance. However, school WASH coverage in developing countries remains low. This study aimed to assess the adequacy of WASH services in Addis Ababa, Ethiopia. Methods: A school-based quantitative cross-sectional study was conducted from January to March 2020 in 98 schools. A multistage sampling technique was used to select schools included in the study. Data were collected using observational checklists and pretested interviewer-administered questionnaires. We entered the data into EPI Info version 7.2.2.6 and analyzed using SPSS 22.0. Logistic regression was used to examine the associated factors with school WASH services. Results: The basic school water, sanitation, and hygiene services were found to be 65.3%, 31.6%, and 36.7%, respectively. The facility-to-student ratio was 1:48 for drinking water point, 1:59 for toilet stance, and 1:147 for handwashing point. The analysis of facilities access by sex revealed that the toilet to student ratio was 1:68 for females and 1:49 for males, whereas the handwashing point-to-student ratio was 1:179 for females and 1:114 for males, indicating disparities in facilities access by sex. The non-functionality rates for drinking water, toilets, and handwashing facilities were 22.5%, 8%, and 19.5%, respectively. School ownership was significantly associated with the availability of basic water services [COR = 4.6, 95% CI: 1.466-14.426] and basic sanitation services [COR = 15, 95% CI: 3.27-68.28]. Moreover, the results demonstrate training on WASH [COR = 5, 95% CI: 1.087-23.018] and teaching programs on WASH [COR = 0.21, 95% CI: 0.056-0.810] were significantly associated with basic hygiene services. Conclusions: The provision of WASH facilities and services in schools was inadequate and not on track to meet the targets of SDG 6. Training, WASH education program, and stakeholder commitment and cooperation at all levels are required to achieve the goal.